Predictors of inadequate bowel preparation in older patients undergoing colonoscopy: a systematic review and meta-analysis - Zhang, Yuanyuan; Wang, Lining; Wu, Wenbi; Zhang, Shi; Zhang, Min; She, Wenjing; Cheng, Qianqian; Chen, Nana; Fan, Pengxia; Du, Yuxin; Song, Haiyan; Hu, Xianyu; et al. (Elsevier Ltd, 2024)
Background: Factors that predict the quality of bowel preparation in older adults are unclear, and current guidelines do not provide specific recommendations. Objective: This meta-analysis aimed to identify risk factors for inadequate bowel preparation in older patients. Methods: PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, and VIP databases were searched from their inception to February 2023. Cohort and cross-sectional studies exploring the risk factors for inadequate bowel preparation were included in this systematic review. Odds ratio (OR) values from individual studies were pooled using fixed-effects and random-effects models. In addition, a sensitivity analysis and assessment of publication bias were performed. Results: This meta-analysis included six studies (n = 1553) on previous abdominal surgery, six studies (n = 1494) on constipation, seven studies (n = 1505) on diabetes, eight studies (n = 2093) on non-compliance with the diet regimen, seven studies (n = 1350) on incomplete intake of laxative, and nine studies (n = 2163) on inadequate exercise during preparation. The pooled analysis showed that history of abdominal surgery (OR = 2.72; 95 confidence interval, CI: 2.07 to 3.56), constipation (OR = 3.56, 95 CI: 2.41 to 5.25), diabetes (OR = 2.54, 95 CI: 1.81 to 3.57), non-compliance with the diet regimen (OR = 2.51, 95 CI: 1.96 to 3.21), incomplete intake of laxative (OR = 2.43, 95 CI: 1.60 to 3.67), and inadequate exercise during preparation (OR = 3.13, 95 CI: 2.39 to 4.11) were independent risk factors for inadequate bowel preparation in older patients undergoing colonoscopy. Conclusions: Three comorbid factors and three behavioral factors were significantly associated with inadequate bowel preparation in older adults. This meta-analysis provides valuable information for developing predictive models of poor bowel preparation.